A ANALISIS KEPUASAN DAN MOTIVASI KONSUMEN TERHADAP PRODUK OLAHAN SEAFOOD DI TOKO KALISHA FROZEN FOOD KOTA SAMARINDA: ANALISIS KEPUASAN DAN MOTIVASI KONSUMEN TERHADAP PRODUK OLAHAN SEAFOOD - Rahman, Odhy Febrianda; Haqiqiansyah, Gusti; Oktawati, Nurul Ovia (Jurnal Pembangunan Perikanan dan Agribisnis, 2024)
Odhy Pebrianda Rahman, 2023. Analysis of Consumer Satisfaction and Motivation for Processed Seafood Products at Kalisha Frozen Food Store in Samarinda City (guided by Gusti Haqiqiansyah and Nurul Ovia Oktawati) This study focuses on analyzing consumer satisfaction and motivation, the purpose of this study is to analyze the level of consumer satisfaction in purchasing processed seafood products and find out consumer motivation to buy processed seafood products at Kalisha Frozen Food Store in Samarinda City. The data used consists of primary and secondary data. Primary data were collected from interviews with 30 respondents using the accidental sampling method. The analysis used in this study is the mean and consumer satisfaction index. The results showed that consumer reaction in buying processed seafood products at Kalisha Frozen Food Store was very satisfied with the consumer satisfaction index was 84.9% (>66.01). Kalisha Frozen Food Store Consumer Satisfaction 1) Consumers want to recommend processed seafood products at Kalisha Frozen Food Store , to relatives or other people with the highest score, namely Strongly agree 2) Consumers always talk about processed seafood products at Kalisha Frozen Food Store because they are delicious and of good quality with the highest score agreeing 3) Consumers want to come and buy back processed products The seafood at Kalisha Frozen Food Shop with the highest score is very agreeable. Consumer motivation rationally in buying processed seafood products at Kalisha Frozen Food Store is quality processed seafood products, processed seafood products are very tasty and delicious and consumers want to know whether the quality of the products offered is in accordance with what is promoted at Kalisha Frozen Food Store while consumer motivation is emotional in buying processed seafood products at Kalisha Frozen Food Store is because the taste of processed seafood products at Kalisha Frozen Food Store is according to contemporary tastes, Consumers feel safe when buying processed seafood products at Kalisha Frozen Food Store because the store is equipped with CCTV cameras and Consumers feel that the service at Kalisha Frozen Food Store is excellent so that consumers feel comfortable.